2004
DOI: 10.1021/nl0351542
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of “Branched” Gold Nanocrystals

Abstract: We report the synthesis of new "branched" gold nanocrystals in high yield (over 90%) via a wet-chemical route. The branched nanocrystals exhibit a shape-dependent plasmon resonance that is red-shifted by 130−180 nm from the spherical particle wavelength. Discrete dipole approximation (DDA) calculations qualitatively replicate the observed optical extinction spectra of the nanocrystals, indicating that the surface plasmon resonance is mainly determined by in-plane dipole excitation associated with the sharp tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
485
3
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(526 citation statements)
references
References 27 publications
23
485
3
15
Order By: Relevance
“…Silver nanoparticles can be synthesized with controlled shape and optical properties guided by optical illumination [18]. More complex architectures have also been described, including gold nanocages [19][20][21], elongated core-shell geometries [22] and gold nanostars [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Silver nanoparticles can be synthesized with controlled shape and optical properties guided by optical illumination [18]. More complex architectures have also been described, including gold nanocages [19][20][21], elongated core-shell geometries [22] and gold nanostars [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…The optical properties of a metallic nanoparticle are determined by its plasmon resonances, which are strongly dependent on particle geometry. The structural tunability of plasmon resonances has been one of the reasons for the growing interest in a rapidly expanding array of nanoparticle geometries, such as nanorods (1,2), nanorings (3), nanocubes (4,5), triangular nanoprisms (6)(7)(8), nanoshells (9), and branched nanocrystals (10,11). The resonant excitation of plasmons can lead to large local enhancements of the incident electromagnetic field at the nanoparticle surface, resulting in dramatically large enhancements of the cross section for nonlinear optical spectroscopies such as surface-enhanced Raman scattering (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Scientist gained significant control both the over size [7] and surfaces [8][9][10][11][12] for nanoparticles. They have demonstrated that anisotropy in nanostructure like triangular prisms [13][14][15][16][17][18], nanoscale rods [19][20][21][22][23][24][25][26], nanoshells [27][28][29][30][31], multipods [32][33][34], disks [35][36][37][38][39] and cubes [40][41][42] shows better performance over solid spheres. …”
Section: Nanomaterials and Nanotechnologymentioning
confidence: 99%